QUIS INTERAKTIF MATEMATIKA TEBAK GAMBAR TINGKAT SD KELAS 1 DAN 2 BERBASIS POWER POINT - Basrul Abdul Majid; Fitri Yanti M (Yayasan Hurriah, Banda Aceh, 2022)
English: Learning mathematics at this time still many students do not like and feel bored in learning mathematics, this could be due to teachers who cannot convey the material well, students who are bored and lazy in learning mathematics, or students who have difficulty understanding the explanations from the teacher. So here the researcher wants to design an interactive math quiz application based on guessing pictures, the goal is that students who take part in math learning do not feel bored in answering the questions given by the teacher and also help students in imagining the pictures in this picture-guessing learning quiz. There are several models used for the development of an interactive math quiz application based on guessing pictures, namely: Concept, Design, Material Collecting, and Assembly. After the system is used by the user, the child continues with the system testing on an interactive math quiz for shooting pictures for elementary school children based on Power Point. Bahasa: Pembelajaran matematika pada saat ini masih saja banyak siswa tidak menyukai dan merasa bosan pada pembelajaran matematika, ini bisa jadi dikarenakan guru yang belum mampu menyampaikan materi dengan baik, siswa yang bosan dan malas dalam belajar matematika, atau siswa yang susah mengerti penjelasan dari guru. Jadi disini peneliti ingin merancang aplikasi quis interkatif matematika berbasis tebak gambar, tujuannya supaya siswa yang mengikuti pembelajaran matematika tidak merasa bosan dalam menjawab soal yang diberikan guru dan juga membantu siswa dalam berimajinasi tentang gambar-gambar yang ada pada quis pembelajaran berbasis tebak gambar ini. ada beberapa model yang digunakan untuk pengembangan aplikasi quis interaktif matematika berbasis tebak gambar yaitu : Concept, Design, Material Collecting, dan Assembly. Setelah sistem digunakan oleh user, maka selanjutnya dilakukan dengan pengujian sistem pada quis interaktif matematika tembak gambar untuk anak sekolah SD Berbasis Power Point.